(NoB]AQ GEOLOGIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NmILXNI^UK(B, (NwIKTOR sTEPANOWI^s; (NaRABADVI(B, (NmIHAIL sTEPANOWI^s ((NmOSKWA (B:s (NnEDRA(B,s, 1989)
(NuKAZ(B. (NTERMINOW(B: (NS(B. 326-330s
(NbIBLIOGR(B.: (NS(B. 325s
Keywords: (NgEOLOGIQs